Magnolol inhibits venous remodeling in mice - Kuk, Hanna (Sci Rep, 2017)
Due to gravity the venous vasculature in the lower extremities is exposed to elevated pressure levels which may be amplified by obesity or pregnancy. As a consequence, venules dilate and may be slowly transformed into varicose or spider veins. In fact, chronically elevated venous pressure was sufficient to cause the corkscrew-like enlargement of superficial veins in mice. We hypothesized that biomechanical activation of endothelial cells contributes to this process and investigated the inhibitory capacity of Magnolol in this context – a natural compound that features multiple properties counteracting cellular stress. While Magnolol did not influence endothelial capillary sprout formation, it interfered with proliferation, ERK1/2 activity, gelatinase activity as well as baseline production of reactive oxygen species in these cells or murine veins. The anti-oxidative and anti-proliferative capacity of Magnolol was mediated through stimulation of heme oxygenase-1 expression. Finally, local transdermal application of Magnolol attenuated pressure-mediated development of varicose/spider veins in mice and was accompanied by the absence of proliferating and MMP-2 positive endothelial cells. Collectively, our data identified Magnolol as a potent inhibitor of biomechanically evoked endothelial cell activity during pressure-mediated venous remodeling processes which contribute to the development of varicose and spider veins.